Through the Review of Hydrogen, Neutrons and Black Holes, An Explanation of Black Matter as Constituted Only by Neutron Stars and Black Holes is Proposed. - Cruz-Gómez, M. Javier (European Journal of Applied Sciences, 2023)
Using the diameters of a hydrogen molecule, H2, a hydrogen atom, H, and of a neutron, N, it is quantified how the densities increase: a). When the empty space between the molecules of H2 at standard conditions of temperature and pressure is eliminated to form solid H2, and b). When the empty space between the electrons and nuclei of an atom is eliminated to form only neutrons. Using the mass of an average neutron star of 1.8 solar masses it is shown how heavy this matter is, due to its high density of 6.46x1014 g/cc. Using the mass and volume of the quarks and of the quarks and gluons inside the neutron it is explored where the mass of a 5 solar mass black hole is located inside the volume delimited by the Schwarzschild radius. Next it is proposed the theory that what is called dark matter is a high number of neutron stars and black holes, equivalent to one of any of them per about each star in the actual universe.